Lifetime-Based Discontinuous PWM for Cascaded H-Bridge Converters - Anas Ibrahim; Mohamed Salem; Tomonobu Senjyu; Soichiro Ueda; Dahaman Ishak; Mahmood Swadi (IEEE Access)
The cascaded H-bridge (CHB) is an attractive converter topology because it can provide voltage and power scalability. However, due to the difference in electrical and thermal characteristics of power devices, the CHB can be composed of cells with unequal remaining useful lifetime (RUL). In this paper, a PWM strategy is proposed to manage the lifetime of individual cells within a single-phase CHB by controlling the thermal stress of power devices. The proposed PWM has two variants of modulation signals. The discontinuous modulation (DM) which reduces the thermal stress of a cell and the compensating modulation (CM) for removing the offset voltage introduced by DM. Based on the accumulated damages of cells, the modulation signals are actively updated to achieve equalized RUL. The benefit of the proposed PWM is that the power transmission of cells is not affected by the clamping region of the DM. This is achieved by introducing a factor C during the unclamped region which reduce the fundamental voltage by the same amount the clamping region causes it to increase. The experimental result verifies the impact of the proposed PWM on the power transmission of cells. Furthermore, a long-term study is provided in simulation to validate the lifetime equalization of cells.